INFLUENCE OF PRODUCT QUALITY, PRICE PERCEPTION, AND QUALITY OF SERVICE, ON SMARTFREN REPURCHASING INTEREST IN THE COVID-19 PANDEMIC (Survey of Smartfren Internet Service Users in the Special Region of Yogyakarta) - Laksana, Dwi Hari; Al Adam, Izzat Dani; Istanto, Yuni (Journal of International Conference Proceedings, 2022)
This study aims to determine the effect of product quality, price perception, and service quality on repurchase interest This research method uses quantitative methods with a survey approach. The sample in this study amounted to 120 respondents. The sampling technique in this study used a non-probability sampling technique with purpose sampling with the criteria of respondents being smart consumers who live in the Special Region of Yogyakarta and have made purchases three times during the covid-19 pandemic. The results of this study indicate that product quality, price perception, and service quality together have a positive and significant impact on the intention to repurchase Smartfren internet services in the Special Region of Yogyakarta during the covid-19 pandemic. Keywords: Product Quality, Price Perception, Service Quality, Repurchase Interest,